Potensi Ekspor Teh Indonesia ke Malaysia - Arifianti, Adek Irma; Bachtiar, Arief; Asmara, Kiky (Peneliti.net, 2023)
International trade is trading activity between countries in which there are activities such as exports and imports. Export is an activity of selling goods abroad. For exports alone, Indonesia is one of the 5th largest tea exporters in the world. For export destination countries, Indonesia has already exported tea to Malaysia. With a number of things which include, geography, climate, culture, politics and law, infrastructure, economy, and competitors make the basis for Indonesia to export to Malaysia. The research method used is qualitative research using several research libraries such as BPS and Trademap. The conclusion from the results of this study is that the volume of export demand is directly proportional to the value, that is, if the export volume increases, the value will also increase and vice versa. But in terms of price, it is inversely proportional to the volume of export demand, that is, if the price increases, the volume of export demand will decrease. And vice versa if the price decreases then the volume of export demand will increase.